Recent Progress and Advances of Multi-Stimuli-Responsive Dendrimers in Drug Delivery for Cancer Treatment - Ngoc Thuy Trang Le; Thi Nhu Quynh Nguyen; Van Du Cao; Duc Thuan Hoang; Van Cuong Ngo; Thai Thanh Hoang Thi (Pharmaceutics, 2019)
Despite the fact that nanocarriers as drug delivery systems overcome the limitation of chemotherapy, the leakage of encapsulated drugs during the delivery process to the target site can still cause toxic effects to healthy cells in other tissues and organs in the body. Controlling drug release at the target site, responding to stimuli that originated from internal changes within the body, as well as stimuli manipulated by external sources has recently received significant attention. Owning to the spherical shape and porous structure, dendrimer is utilized as a material for drug delivery. Moreover, the surface region of dendrimer has various moieties facilitating the surface functionalization to develop the desired material. Therefore, multi-stimuli-responsive dendrimers or ‘smart’ dendrimers that respond to more than two stimuli will be an inspired attempt to achieve the site-specific release and reduce as much as possible the side effects of the drug. The aim of this review was to delve much deeper into the recent progress of multi-stimuli-responsive dendrimers in the delivery of anticancer drugs in addition to the major potential challenges.